A waveform-similarity-based protection scheme for the VSC-HVDC transmission lines. (January 2023) - Zhang, Yuhan; Wang, Shunliang; Liu, Tianqi
Highlights: The non-unit protection based on the traveling waveform similarity is proposed for the VSC-HVDC transmission line. The traveling waveform similarity differences between internal and external faults are proved in theory. The protection scheme can identify the double-pole-to-ground fault with its positive-pole fault resistance unequal to negative-pole fault resistance accurately. The scheme provides high performance considering the possible influence factors. The method improves the protection selectivity, reliability, rapidity, and sensitivity. Abstract: The protection for the voltage source converter based high voltage direct current (VSC-HVDC) transmission lines must detect the faulty DC lines and faulty poles within a few milliseconds, because the fault current rises quickly. The traditional protections are easily influenced by fault resistance and signal noise. What is worse, the double-pole-to-ground (DPG) fault with its positive-pole fault resistance unequal to negative-pole fault resistance cannot be detected accurately. To solve the problems, a non-unit protection scheme based on the waveform similarity and wavelet transform modulus maximum (WTMM) theories for the VSC-HVDC lines is proposed in this paper. A four-terminal VSC-HVDC power network is modeled in PSCAD to verify the protection. Extensive simulations of various fault situations prove that the protection scheme can detect high-fault-resistance, DPG, and remote faults. Moreover, it is insensitive to the sampling frequency, signal noise, smoothing reactor, and start delay. Furthermore, it can meet the rapidity requirement. Therefore, the proposed protection can identify the DC faults accurately, which minimizes the disturbance to power grids and improves system security and stability.